An algebra problem by Satwik Murarka

Algebra Level 3

2 ( 2 + 6 ) 3 2 + 3 \large \dfrac{2 (\sqrt2 + \sqrt6)}{3\sqrt{2 + \sqrt3}}

If the expression above simplifies to a b \dfrac ab , where a a and b b are coprime positive integers, find a + b a+b .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Satwik Murarka
Sep 26, 2016

Simplifying the denominator first 3 × ( 2 + 3 ) = 3 × ( 3 + 1 ) 2 Multiplying numerator by √2 2 × ( 2 + 6 ) = 4 × ( 3 + 1 ) Therefore, we get 4 × ( 3 + 1 ) 3 × ( 3 + 1 ) = 4 3 4 + 3 = 7 \text{Simplifying the denominator first}\\ 3\times(\sqrt{2+\sqrt{3}})=\frac{3\times(\sqrt{3}+1)}{\sqrt{2}}\\ \text{Multiplying numerator by √2}\\ 2\times(\sqrt{2}+\sqrt{6})=4\times(\sqrt{3}+1)\\ \text{Therefore, we get}\\ \frac{4\times(\sqrt{3}+1)}{3\times(\sqrt{3}+1)}=\frac{4}{3}\\ 4+3=\boxed{7}

Anandmay Patel
Sep 27, 2016

Let the given expression be equal to x \text{Let the given expression be equal to x} .

Then, \text{Then,} x 2 = 2 3 × 2 3 × ( 2 + 6 ) 2 ( 2 + 3 ) x^2=\dfrac23\times\dfrac23\times\dfrac{(\sqrt2+\sqrt6)^2}{(2+\sqrt3)}

So, \text{So,} x 2 = 4 9 × ( 8 + 4 2 ) = 4 ( 2 + 3 ) ( 2 + 3 ) = 4 9 × 4 x^2=\dfrac49\times\dfrac{(8+4\sqrt2)=4(2+\sqrt3)}{(2+\sqrt3)}=\dfrac49\times4

Therefore, \text{Therefore,} x = ( 4 × 4 9 ) = 4 3 x=\sqrt{\left(\dfrac{4\times4}9\right)}=\dfrac43

Finally we have got the fraction,already in its simplest form,thus,the answer is \text{Finally we have got the fraction,already in its simplest form,thus,the answer is} 4+3=7 \text{4+3=7}

Very good alternative method to solve the problem.

Satwik Murarka - 4 years, 8 months ago

Log in to reply

Thanks! Yours too:)

Anandmay Patel - 4 years, 8 months ago
Tapas Mazumdar
Sep 27, 2016

2 ( 2 + 6 ) 3 2 + 3 = 2 2 ( 1 + 3 ) 3 3 + 1 3 1 = 2 2 3 + 1 3 3 1 = 2 2 3 1 3 = 2 2 × 2 3 = 4 3 = a b a = 4 and b = 3 a + b = 7 \begin{aligned} \dfrac{2 (\sqrt2 + \sqrt6)}{3\sqrt{2 + \sqrt3}} & = \dfrac{2 \sqrt2 (1 + \sqrt3)}{3 \sqrt{\frac{\sqrt3 + 1}{\sqrt3 -1}}} \\ \\ & = \dfrac{2\sqrt2 \sqrt{\sqrt3 + 1}}{\frac{3}{\sqrt{\sqrt3 -1}}} \\ \\ & = \dfrac{2\sqrt2 \sqrt{3-1}}{3} \\ \\ & = \dfrac{2\sqrt2 \times \sqrt2}{3} \\ \\ & = \dfrac{4}{3} = \dfrac{a}{b} \end{aligned} \\ \\ \therefore a =4 ~ \text{and} ~ b=3 \implies a+b = \boxed{7}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...